PERAN EMOTIONAL INTELLIGENCE SEBAGAI MEDIATOR PENGARUH SELF-COMPASSION TERHADAP MARITAL ADJUSMENT BEDA BUDAYA - Natris Idriyani (Mimbar Agama Budaya, 2020)
Abstract. The purpose of this study was to test the fit model of the emotional intelligence model as a mediator variable the influence of self-compassion on the marital adjustment of women with couples from different cultures. The dynamics that occur in women who have intercultural partners are in the spotlight in terms of their ability to adjust in marriage, in order to achieve a sakinah mawaddah wa rahmah marriage. This study uses a causal relationship design with a quantitative approach. The study participants were 220 women who have partners from different cultures. The sampling technique used was purposive sampling. The measuring instrument used is a modification of the Marital Adjustment Questionaire (MAQ), Self Compassion Scale (SCS) and Assesing Emotional Scale (AES). Testing the validity of the measuring instrument used the Confirmatory Factor Analysis (CFA) technique and the data analysis technique used the Structural Equotion Model (SEM). The results showed that the model fit with data. The direct effect of self compassion on the marital adjustment of married women for different cultures is -0.17. Meanwhile, the indirect effect of self compassion on the marital adjustment of married women with different cultures through emotional intelligence is 0.209. This shows that emotional intelligence acts as a mediator variable for the influence between self-compassion and marital adjustments on women’s with couples from different cultures. This research recommends the importance of this model as a reference for making special pre-marital training programs for married couples with different cultures, by prioritizing the role of emotional intelligence.  Abstrak. Tujuan penleitian ini adalah menguji fit model emotional intelligence sebagai mediator pengaruh self compassion terhadap marital adjustment wanita dengan pasangan beda budaya. Dinamika yang terjadi pada wanita yang memiliki pasangan beda budaya menjadi sorotan dalam hal kemampuan untuk menyesuaikan dalam pernikahan, guna tercapainya pernikahan yang sakinah mawaddah wa rahmah. Penelitian ini menggunakan desain causal relationship dengan pendekatan kuantitatif. Partisipan penelitian sebanyak 220 wanita yang memiliki pasangan beda budaya. Teknik sampling yang digunakan adalah purposive sampling. Alat ukur yang digunakan adalah modifikasi dari Marital Adjustment Questionaire (MAQ), Self Compassion Scale (SCS) dan Assesing Emotional Scale (AES). Pengujian validitas alat ukur menggunakan teknik Confirmatory Factor Analysis (CFA) dengan teknik analisa data menggunakan Structural Equotion Model (SEM). Hasil penelitian menunjukan bahwa model fit dengan data. Pengaruh langsung self compassion terhadap marital adjustment wanita menikah beda budaya sebesar -0.17. Sedangkan pengaruh tidak langsung self compassion terhadap marital adjustment wanita menikah beda budaya melalui emotional intelligence sebesar 0.209. Hal ini menunjukan bahwa emotional intelligence berperan sebagai mediator variabel pengaruh antara self compassion terhadap marital adjustment wanita dengan pasangan beda budaya. Riset ini merekomendasikan pentingnya model ini untuk menjadi acuan bagi pembuatan program pelatihan pranikah khusus bagi pasangan menikah beda budaya, dengan mengutamakan peran emotional intelligence.